Innovating construction law : towards the digital age - Mason, Jim (James Robert) (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Innovating Construction Law: Towards the Digital Age draws together current and emerging technologies and examines how legal practice in the construction industry can respond to the challenges to its existing arrangements"--
Introduction -- Limitations of the construction industry's approach -- Limitations in the legal approach -- The smart contract in construction -- Perceptions in the construction industry of smart contracts? -- Smart contracts and the legal system -- New collaborative directions -- Background provisions -- The steps in between -- Building information modelling (BIM) -- Online dispute resolution -- Conclusions and next steps.
OCLC-licensed vendor bibliographic record.
Keywords: Building laws; Construction industry -- Law and legislation; Construction contracts; LAW / Construction